2013
DOI: 10.1074/jbc.m113.470617
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3 Growth Inhibition of Colonic Cells Is Dependent on Intraepithelial Lipid Droplet Density

Abstract: Background:The loss of FOXO3 is critical for tumor growth. Results: FOXO3 and lipid droplets (LDs) have feedback regulation, and the loss of FOXO3 leading to increased LDs is key in the growth of colonic cells. Conclusion: FOXO3-dependent LDs provide lipid energy critical for cellular growth. Significance: Identifying regulators of cellular lipid energy could provide new targets for colon cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 53 publications
5
59
0
Order By: Relevance
“…In our system, DHA stimulated SIRT6 activation (Figure 2A, B), which resulted in apoptosis ( Figure 3A, B). This observation is supported by previous reports, which showed that SIRT6 decreases transcriptional activity at forkhead box O3 (FOXO3a) and c-Jun promoters, which regulate genes such as AKT and GSK-3β, promoting apoptotic cell death [34,35]. It is possible that the mechanism for DHA-induced apoptosis involves FOXO3a or c-Jun.…”
Section: Discussionsupporting
confidence: 86%
“…In our system, DHA stimulated SIRT6 activation (Figure 2A, B), which resulted in apoptosis ( Figure 3A, B). This observation is supported by previous reports, which showed that SIRT6 decreases transcriptional activity at forkhead box O3 (FOXO3a) and c-Jun promoters, which regulate genes such as AKT and GSK-3β, promoting apoptotic cell death [34,35]. It is possible that the mechanism for DHA-induced apoptosis involves FOXO3a or c-Jun.…”
Section: Discussionsupporting
confidence: 86%
“…This is reminiscent of the "sibling rivalry" between HIF1α and HIF2α documented across various ccRCC models ( 7 ). Similar results were seen in a mouse colon tumor model, where tumor proliferation was PLIN2-and lipid droplet-dependent, whereas the HIF1α target FOXO3 induced tumor death and PLIN2 and lipid depletion ( 8 ). However, interactions between HIF isoforms are often cell type specifi c. PLIN2 is HIF1α dependent but not HIF2α dependent in glioblastoma and breast cancer cell lines ( 3 ).…”
supporting
confidence: 63%
“…Fatty acid treatment also induces DGAT2 to associate with LD and take part in LD expansion (Harris et al, 2011; Jin et al, 2014; McFie et al, 2014; Wilfling et al, 2013; Xu et al, 2012). In addition to TG storage and control of energy metabolism, LD are involved in cancer cachexia and cancer cell growth (Qi et al, 2013; Yue et al, 2014). We now can add acylceramide to this group of storage lipids, and suggest that hydrolysis of acylceramide at its ester link by lipases may constitute a source of ceramide generation.…”
Section: Discussionmentioning
confidence: 99%